Descriptive Analysis of the Fear of Missing Out (FOMO) Phenomenon: The Bitcoin Trading Decisions of Students in Semarang City - Bahri, Saiful; Aeni, Deswita Siti Nurul (Faculty of Economics and Business UNTAG Semarang, 2025)
The Fear of Missing Out (FOMO) phenomenon in crypto asset trading activities such as Bitcoin is increasingly prevalent among the younger generation, especially students. This study aims to describe the level of FOMO experienced by students in Semarang City who actively trade Bitcoin and the factors that influence it. The research method used is a quantitative approach with a descriptive survey design. Data collection was carried out by distributing Likert-based questionnaires to 100 students aged 17 to 23 years spread across various universities in Semarang City. The results showed that most respondents experienced moderate to high levels of FOMO, which were triggered by social media factors, peer influence, and market price volatility. This study is expected to be the basis for wiser digital financial education among students.